PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR AND SHARE TERHADAP KEMAMPUAN PEMECAHAN MASALAH SISWA PADA MATERI BENTUK ALJABAR KELAS VII MTS YPKS PADANGSIDIMPUAN - Akid Nasution, Muhammad; Panjaitan, Agus Makmur; Nilasari Harahap, Adek (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2021)
The research aims to determine the effect of implementing the cooperatif learning model type Think Pair and Share.This type of research is Quasi Research Experiments. The subjects of the study were classes VII-1 and VII-2 of 40 people. Women as many as 20 men and 20 men.The object taken in this study is the use of TPS learning models in an effect of implementing of student learning concepts on algebraic subjects.the test results against the math problem solving level students obtained an average score of experimental group = 78.35 with the criteria